‘All is well’: The Construction of Martyrdom in the Diary of Emily Hawley Gillespie (1838-1888) - Claire SORIN (E-REA)
Emily Hawley Gillespie’s diaries offer a rare insight into the daily life of a farmer’s wife in 19th-century Iowa and into the intricate processes of diary writing and memory shaping. This extraordinarily voluminous journal, kept over three decades, was not meant to be a mere record of life and work but an autobiographical legacy destined to testify to Emily Gillespie’s intellectual abilities and domestic martyrdom in her slowly disintegrating home. Hovering between revelation and secrecy, the diary seeks to immortalize its author as an ideal mother, patient wife and perfect invalid. This essay, which focuses on the last years of the diarist’s life, explores how the writing of pain and suffering seeks to sublimate the present and shape the future. This was done with the collaboration of the author’s daughter who revised, transcribed and transmitted Gillespie’s notebooks with a view to memorialize her mother.